Multimodal Heartbeat and Compression Optical Coherence Elastography for Mapping Corneal Biomechanics - Nair, Achuth; Singh, Manmohan; Aglyamov, Salavat R.; Larin, Kirill V. (Frontiers in Medicine, 2022)
The biomechanical properties of the cornea have a profound influence on the health, structural integrity, and function of the eye. Understanding these properties may be critical for diagnosis and identifying disease pathogenesis. This work demonstrates how two different elastography techniques can be combined for a multimodal approach to measuring corneal biomechanical properties. Heartbeat optical coherence elastography (Hb-OCE) and compression OCE were performed simultaneously to measure the biomechanical properties of the cornea in an in vivo rabbit model. Measurements were further performed after collagen crosslinking to demonstrate how the combined technique can be used to measure changes in corneal stiffness and map mechanical contrast. The results of this work further suggest that measurements from Hb-OCE and compression OCE are comparable, meaning that Hb-OCE and compression OCE may be used interchangeably despite distinct differences in both techniques.